The Exploration of Need Analysis In English Language Teaching : Teaching Reading Skill - Gawa, Dila Maya Titian (Department of English Language Education, UIN Sunan Ampel Surabaya, 2022)
Needs analysis is generally believed to be important in ESP/EAP context because it enables practitioners and materials writers to find out about their real learners' needs. Therefore, the aim of the study is to explore the need analysis in teaching reading in English language teaching. Needs analysis has to be encouraged and leaners' needs has to be explored. Teacher has to be involved in doing the need analysis. The results demonstrate that EFL learners have difficulty in reading especially to comprehend the reading. Keywords: need analysis, reading